A maturity assessment model for manufacturing systems. Issue 5 (19th February 2018) - Vivares, Jorge A.; Sarache, William; E. Hurtado, Jorge
Abstract : Purpose: Assessment of manufacturing systems provides a baseline for manufacturing strategy (MS) formulation. The purpose of this paper is to develop and propose a maturity assessment model for manufacturing systems (MAMMS). The MAMMS provides a maturity index, in order to establish manufacturing system performance on five possible levels: preinfantile, infantile, industry average, adult, and world class manufacturing. Design/methodology/approach: Three main steps were taken: MAMMS design; maturity-level assessment in two companies; and MAMMS validation. Based on an action-research process, several research tools, such as surveys, expert panels, and immersion in two manufacturing companies, were used. Findings: By integrating 79 variables into a maturity index, the maturity level for two manufacturing companies was obtained. Considering three main components (competitive priorities, manufacturing levers, and manufacturing's strategic role), the analyzed companies showed a performance at the average industry level. According to participants, the MAMMS is a valuable tool to support decision making in MS. Practical implications: Empirical evidence supports the relevance of the proposed MAMMS and its practical usefulness. In particular, the maturity index identifies strengths and weaknesses in the manufacturing system, providing a baseline from which to deploy MS. Originality/value: The literature review shows a lack of contributions regarding maturity models, particularly, the non-existence of maturity assessment models for manufacturing systems. The proposed MAMMS is a valuable tool to support decision making in MS. Also, this paper contributes to understanding the action-research paradigm, for further research in operations management.